VOCs and odor gas purification photo-thermal catalytic material without external heat source
Patent Information
- Application Number
- CN202410993578.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-07-24
AI Technical Summary
[0006]为了克服上述现有技术的不足,本发明提出了一种用于高效去除污染物并可视化光热催化过程的光热催化材料,该催化材料由钨酸铋(Bi2WO6)的衍生物(Bi@BWO)与氯氧铋(BiOCl,或BOC)和硫氧铋(Bi2O2S,或BOS)形成的界面紧密结合的异质结负载在改性多孔吸附材料上制得,在无需外加热源条件下即可对多种VOCs和臭味气体实现高效净化,解决了普通钨酸铋材料光热催化效率不高,对有机废气和臭气去除不彻底的问题,在室内空气净化相关领域具有重要的应用前景
本发明公开了一种用于高效去除污染物并可视化光热催化过程的复合光热催化材料,该催化材料由钨酸铋(Bi2WO6)的衍生物(Bi@BWO)与氯氧铋(BiOCl,或BOC)和硫氧铋(Bi2O2S,或BOS)在界面形成紧密结合的异质结负载在改性多孔吸附材料上所得。具体制备方法为:先将钨酸盐和铋盐溶解到溶剂中,通过控制两种盐的添加比例,并引入阳离子表面活性剂和乙二醇,制备得到Bi2WO6的衍生物(Bi@BWO),然后通过调控上述溶液的pH,并加入一定比例的硫代乙酰胺(TAA),进而获得由Bi2WO6的衍生物与氯氧铋(BiOCl)和硫氧铋(Bi2O2S)形成的异质结(Bi@BWO/BOC/BOS)。该异质结催化剂具有强光热效应和光致变色特性。最后,将该异质结材料与改性多孔吸附材料结合形成复合光热催化材料。该催化剂具备突出的吸附性能,在无需外加热源条件下即可对多种VOCs和臭味气体实现高效净化,适合推广应用于室内空气净化相关领域。此外,该复合光热催化材料的制备工艺简单,制备成本和原料成本都很低廉,也无其它有毒副产物,使用范围广泛。
Smart Images

Figure CN118949971B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of air pollution control technology, specifically relating to a photothermal catalytic material for purifying VOCs and odor gases without the need for an external heat source. Background Technology
[0002] The odor primarily originates from hundreds of organic malodorous substances produced during waste fermentation, including ammonia, hydrogen sulfide, methanethiol, dimethyl sulfide, dimethyl sulfide, trimethylamine, and carbon disulfide. Although the absolute doses of these malodorous substances are small and difficult to detect with conventional instruments, the human sense of smell is extremely sensitive to them. Meanwhile, VOCs (Volatile Organic Compounds) are widely present in numerous everyday products used in production, residential, and commercial applications, constantly releasing harmful substances into the air, such as formaldehyde and benzene. Like odors, the concentration of VOCs is also very low, and their release mechanisms are often insidious and diverse, sometimes even mixed with odors, making them difficult to detect and distinguish in a timely manner. However, since both odors and VOCs are closely related to people's daily lives and work, the coordinated management of odors and VOCs is of great significance for improving the quality of life and work for the public.
[0003] In recent years, photothermal catalysis technology based on sunlight for treating odors and VOCs has been considered an ideal technology for environmental remediation. However, traditional photothermal catalysts (such as TiO2) have low light energy utilization rates, are prone to photogenerated carrier recombination, and have small specific surface areas, which are not conducive to the adsorption of organic waste gases or odors. In addition, most photothermal catalysts have weak photothermal effects, resulting in low light energy conversion rates, requiring heating conditions to trigger the photothermal catalytic reaction. For example, the bismuth titanate / bismuth / bismuth vanadate composite disclosed in Chinese invention patent CN110368924A can completely catalytically purify typical VOCs such as toluene, xylene, and benzene under visible light irradiation and heating conditions (such as 90°C).
[0004] Bi₂WO₆ is a layered heterojunction with a structure different from traditional photothermal catalysts, which is more conducive to carrier separation. However, ordinary Bi₂WO₆ is prone to interlayer electron-hole recombination, resulting in unsatisfactory catalytic activity and only responding to a limited amount of visible light, with a weak photothermal effect. Therefore, Bi₂WO₆ needs to be modified to obtain a highly active bismuth tungstate photothermal catalyst. Furthermore, single photothermal catalysts often have a small specific surface area, making it difficult to immobilize rapidly flowing organic waste gas, thus resulting in insufficient removal of organic waste gas. Therefore, porous adsorbent materials with strong adsorption properties are needed to improve the interception rate of organic waste gas and odor.
[0005] In summary, given the low photothermal catalytic efficiency of ordinary bismuth tungstate materials and their incomplete removal of organic waste gas and odor, it is necessary to modify bismuth tungstate and couple it with porous adsorbents to develop a composite photothermal catalytic material that can efficiently remove odor and VOCs. Summary of the Invention
[0006] To overcome the shortcomings of the prior art, this invention proposes a photothermal catalytic material for efficient removal of pollutants and visualization of the photothermal catalytic process. This catalytic material is prepared by loading a heterojunction formed by the interface of bismuth tungstate (Bi2WO6) derivative (Bi@BWO), bismuth oxychloride (BiOCl, or BOC), and bismuth oxysulfide (Bi2O2S, or BOS) onto a modified porous adsorbent material. It can achieve efficient purification of various VOCs and odorous gases without the need for an external heat source, solving the problems of low photothermal catalytic efficiency and incomplete removal of organic waste gas and odor by ordinary bismuth tungstate materials. It has important application prospects in the field of indoor air purification.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of this invention provides a method for preparing a composite photothermal catalytic material based on modified bismuth tungstate and a porous adsorbent, the method comprising the following steps: S1. Dissolve cationic surfactant and ethylene glycol in water, then add tungstate and bismuth salt, mix and dissolve, adjust the pH of the solution to 2-10, add thioacetamide, dissolve and carry out hydrothermal reaction, collect the solid product after reaction, wash and dry to obtain Bi@BWO / BOC / BOS photothermal catalyst. S2. After modifying the porous adsorbent by acid and alkali impregnation, the modified porous adsorbent is obtained by drying.
[0008] S3. The Bi@BWO / BOC / BOS photothermal catalyst is mixed with the modified porous adsorbent, dispersed in an adhesive solution, and then coated onto a felt cloth. After drying, the composite photothermal catalytic material is obtained. It should be understood that, in addition to the coating method described in S3, the method of combining the Bi@BWO / BOC / BOS photothermal catalyst with the porous adsorbent can also include electrostatic attraction, electrospinning, impregnation, deposition, precipitation, physical mixing, etc.
[0009] Preferably, the cationic surfactant is selected from at least one of dodecyl dimethyl benzyl ammonium chloride, hexadecyl trimethyl ammonium chloride, octadecyl trimethyl ammonium chloride, glycidyl phenylethyl dichloride, tetradecyl-dimethylpyridine ammonium bromide, and hexadecyl trimethyl ammonium bromide.
[0010] Preferably, the tungstate comprises Na2WO4•2H2O, and the bismuth salt comprises Bi(NO3)3·5H2O.
[0011] Preferably, the solution used to adjust the pH of the solution in S1 is a 12 mol / L HCl solution and a 6 mol / L NaOH solution.
[0012] Preferably, the temperature of the hydrothermal reaction in S1 is 100-250 ℃, the heating rate is 2-10 ℃ / min, and the time is 12-48 h.
[0013] Preferably, the mass ratio of the tungstate, cationic surfactant, and thioacetamide is 250-350:30-300:40-60, and the molar ratio of the bismuth salt to the tungstate is (0.5-3):1.
[0014] Preferably, the porous adsorbent includes activated carbon and molecular sieves, and the felt cloth includes carbon felt, polymer felt, and fiber cloth.
[0015] Preferably, in S2, the pH of the solution during the acid-base impregnation modification of the porous adsorbent is 1-10.
[0016] Preferably, in S3, the mass ratio of the Bi@BWO / BOC / BOS photothermal catalyst to the modified porous adsorbent is (0.2-10):1.
[0017] Preferably, in S3, the adhesive solution is selected from at least one of polyvinyl alcohol, polyvinylpyrrolidone, polyurethane, and epoxy resin.
[0018] The second aspect of the present invention provides a composite photothermal catalytic material based on modified bismuth tungstate and a porous adsorbent, prepared by the preparation method described in the first aspect.
[0019] The catalytic material prepared using the method of this invention exhibits high efficiency in removing VOCs and odors. It can efficiently remove various VOCs such as formaldehyde, toluene, and benzene (for example, the efficiency in removing 100 ppm toluene under full-spectrum irradiation can reach over 97%), and it can also efficiently remove methanethiol odor. It is versatile, stable, and has long-term practicality. Furthermore, it possesses photochromic properties, indicating that the catalyst has exerted its catalytic effect, and exhibits a good photothermal effect with high light energy utilization. This composite photothermal catalytic material solves the problems of low photothermal catalytic efficiency and incomplete removal of organic waste gases and odors associated with ordinary bismuth tungstate materials, and has significant application prospects in the field of indoor air purification.
[0020] The third aspect of this invention provides the application of the composite photothermal catalytic material based on modified bismuth tungstate and porous adsorbent described in the second aspect in the purification of VOCs and odor.
[0021] Compared with the prior art, the beneficial effects of the present invention are: This invention discloses a composite photothermal catalytic material for efficient pollutant removal and visualization of the photothermal catalytic process. This catalytic material is obtained by loading a modified porous adsorbent material with a tightly bonded heterojunction formed at the interface between a bismuth tungstate (Bi2WO6) derivative (Bi@BWO), bismuth oxychloride (BiOCl, or BOC), and bismuth oxysulfide (Bi2O2S, or BOS). The specific preparation method is as follows: First, tungstate and bismuth salt are dissolved in a solvent. By controlling the addition ratio of the two salts and introducing a cationic surfactant and ethylene glycol, a Bi2WO6 derivative (Bi@BWO) is prepared. Then, by adjusting the pH of the solution and adding a certain proportion of thioacetamide (TAA), a heterojunction (Bi@BWO / BOC / BOS) formed by the Bi2WO6 derivative, bismuth oxychloride (BiOCl), and bismuth oxysulfide (Bi2O2S) is obtained. This heterojunction catalyst exhibits strong photothermal effect and photochromic properties. Finally, this heterojunction material is combined with the modified porous adsorbent material to form a composite photothermal catalytic material. This catalyst possesses outstanding adsorption performance, enabling efficient purification of various VOCs and odorous gases without the need for an external heat source, making it suitable for widespread application in indoor air purification. Furthermore, the preparation process of this composite photothermal catalytic material is simple, with low preparation and raw material costs, and it produces no other toxic byproducts, thus broadening its application range. Attached Figure Description
[0022] Figure 1 The XRD spectra of each sample (Bi@BWO / BOC / BOS, BOS, BOC, Bi@BWO, BWO); Figure 2 Thermal images of Bi@BWO / BOC / BOS-M under both dark and lit conditions; Figure 3 The color changes of Bi@BWO / BOC / BOS under no light and with light; Figure 4 The removal rates of toluene by different catalysts (Bi@BWO / BOC / BOS-M, Bi@BWO / BOC / BOS, BWO, Bi@BWO, Bi@BWO / BOC, Bi@BWO / BOS, NKF-6(β) molecular sieve); Figure 5 The formaldehyde removal rates of different catalysts (Bi@BWO / BOC / BOS-M, NKF-6(β) molecular sieve) were measured. Figure 6 The removal rates of methanethiol by different catalysts (Bi@BWO / BOC / BOS-M, NKF-6(β) molecular sieve); Figure 7The removal rates of toluene by different catalysts (Bi@BWO / BOC / BOS-C, activated carbon); Figure 8 The formaldehyde removal rates of different catalysts (Bi@BWO / BOC / BOS-C, activated carbon); Figure 9 The removal rates of methanethiol by different catalysts (Bi@BWO / BOC / BOS-C, activated carbon) are shown. Detailed Implementation
[0023] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0024] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.
[0025] Example 1: Preparation of Bi@BWO / BOC / BOS Coupled Modified Molecular Sieve Felt Composite Photothermal Catalytic Material and Its Application in Toluene Remediation 1. Preparation of Bi@BWO / BOC / BOS coupled modified molecular sieve felt composite photothermal catalytic material (Bi@BWO / BOC / BOS-M): 1) Dissolve 120 mg of octadecyltrimethylammonium chloride in 40 mL of water, then add 300 mg of Na₂WO₄•2H₂O and 829 mg of Bi(NO₃)₃·5H₂O. After stirring for 60 min until completely dissolved, add 30 mL of ethylene glycol, then add 12 mol / L HCl dropwise to adjust the pH of the solution to 3. Next, add 50 mg of thioacetamide, stir for 30 min, and then add 6 mol / L NaOH dropwise to adjust the pH of the solution to 8. Transfer the solution to a 100 mL Teflon-lined stainless steel autoclave for a solvothermal reaction at 150 °C for 24 h at a heating rate of 8 °C / min. After the reaction, collect the solid product by centrifugation, wash three times with water and anhydrous ethanol, and then dry the washed product in a 60 °C oven for 24 h to obtain the Bi@BWO / BOC / BOS catalyst.
[0026] 2) Add 3 g of NKF-6(β) molecular sieve powder to 50 mL of 0.5 mol / L nitric acid solution, stir for 3 h, centrifuge to collect the powder and dry it. Then, mix the dried Bi@BWO / BOC / BOS catalyst with the molecular sieve powder at a mass ratio of 9:2. Then, disperse the resulting mixture thoroughly in a 10 wt.% polyvinyl alcohol aqueous solution by ultrasound. The mass ratio of the mixture to the polyvinyl alcohol aqueous solution is 1:1. Then, 10 mL of the mixed solution is evenly coated onto a 3 cm diameter vinylon polymer felt and dried in an 80℃ oven to obtain a photothermal catalytic material (Bi@BWO / BOC / BOS-M) with adsorption capacity and photochromic properties.
[0027] 2. Performance test of Bi@BWO / BOC / BOS-M catalyst for toluene removal: Take 0.2 g of catalyst and spread it evenly on a 6 cm thick surface. 2 The bottom of the watch glass was then examined, and the watch glass was placed in the reaction vessel and sealed. A toluene-nitrogen-oxygen mixture (N2:O2=3:1) was then introduced into the reaction vessel via bubbling, with the toluene concentration in the reaction vessel being 100 ppm. Full-spectrum light (100 mW / cm²) was then introduced into the reaction vessel for irradiation. 2 Then, during irradiation, the concentration of toluene in the reactor was periodically detected by chromatography, and the toluene content was quantified by Shimadzu chromatography (GC2020).
[0028] In addition, the removal performance of Bi@BWO / BOC / BOS-M for formaldehyde pollutant gas and methanethiol odor gas was also measured.
[0029] Example 2: Preparation of Bi@BWO / BOC / BOS Coupled Modified Activated Carbon Felt Composite Photothermal Catalytic Material and Its Application in Toluene Remediation The difference from Example 1 is that the NKF-6(β) molecular sieve adsorbent is replaced with activated carbon, and the concentration of nitric acid is 0.1 mol / L when the activated carbon is acid-modified, thereby preparing the Bi@BWO / BOC / BOS coupled modified activated carbon felt composite catalyst (Bi@BWO / BOC / BOS-C).
[0030] Similarly, in addition to toluene, the removal performance of Bi@BWO / BOC / BOS-C on formaldehyde pollutant gas and methanethiol odor gas was also determined.
[0031] Comparative Example 1: Preparation of BOS (Bi2O2S) photothermal catalytic material First, 100 mg of octadecyltrimethylammonium chloride was dissolved in 60 mL of deionized water by ultrasonic treatment. Then, 0.24 g of Bi(NO3)3·5H2O was added to the solution under vigorous stirring. After 5 minutes, 0.03 g of TAA was added, and the mixture was stirred for another 5 minutes. Subsequently, 6 mol / L NaOH was added dropwise to adjust the pH of the solution to 8, and the suspension was stirred for another 20 minutes. The solution was then transferred to a 100 mL autoclave lined with polytetrafluoroethylene. The autoclave was placed in an oven at 200 °C for 30 minutes. After thorough washing with deionized water and anhydrous ethanol, the red product BOS (Bi2O2S) was obtained.
[0032] Comparative Example 2: Preparation of BOC (BiOCl) photothermal catalytic material 2 mmol of Bi(NO3)3·5H2O was dissolved in 10 mL of concentrated hydrochloric acid, and the pH of the mixture was adjusted to 7 with 2 mol / L NaOH aqueous solution. The solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner and hydrothermally reacted at 180 °C for 20 hours. After cooling to room temperature, the solution was washed multiple times by centrifugation with deionized water and anhydrous ethanol, and dried overnight in an oven at 80 °C to obtain BiOCl(BOC).
[0033] Comparative Example 3: Preparation of Bi@BWO / BOC / BOS photothermal catalytic material and its application in toluene treatment The difference from Example 1 is that no adsorbent material (NKF-6(β) molecular sieve) was added, and no felt was used.
[0034] Comparative Example 4: Preparation of Bi2WO6 catalytic material and its application in toluene treatment 1. Preparation of photothermal catalytic material Bi2WO6 (or BWO): 120 mg of octadecyltrimethylammonium chloride was dissolved in 70 mL of water, followed by the addition of 300 mg of Na₂WO₄•2H₂O and 729 mg of Bi(NO₃)₃·5H₂O. After stirring for 60 min until completely dissolved, the solution was transferred to a 100 mL Teflon-lined stainless steel autoclave for a solvothermal reaction at 150 °C for 24 h at a heating rate of 8 °C / min. After the reaction, the solid product was collected by centrifugation and washed three times with water and anhydrous ethanol, respectively. The washed product was then dried in a 60 °C oven for 24 h.
[0035] 2. Performance test of Bi2WO6 (BWO) material for toluene removal: 0.2 g of catalyst material was spread evenly on a 6 cm² surface. 2The bottom of the watch glass was then placed inside the reaction vessel and sealed. A toluene-nitrogen-oxygen mixture (N2:O2=3:1) was then introduced into the reaction vessel via bubbling, with the toluene concentration in the reaction vessel being 100 ppm. Finally, full-spectrum light (100 mW / cm²) was introduced into the reaction vessel for irradiation. 2 The toluene concentration in the reactor was periodically monitored using chromatography during irradiation. The toluene content was quantified using a Shimadzu chromatograph (GC2020).
[0036] Comparative Example 5: Preparation of Bi@BWO catalytic material and its application in toluene treatment The difference between preparing Bi@BWO and preparing Bi2WO6 (or BWO) in Comparative Example 4 is that the surfactant was first added to 40 mL of water, followed by 30 mL of ethylene glycol, and the amount of Bi(NO3)3·5H2O was changed to 829 mg. Specifically: 120 mg of octadecyltrimethylammonium chloride was dissolved in 40 mL of water, followed by the addition of 300 mg of Na₂WO₄•2H₂O and 829 mg of Bi(NO₃)₃·5H₂O. After stirring for 60 min until completely dissolved, 30 mL of ethylene glycol was added, and the mixture was stirred for another 30 min. The solution was then transferred to a 100 mL Teflon-lined stainless steel autoclave for a solvothermal reaction at 150 °C for 24 h at a heating rate of 8 °C / min. After the reaction was complete, the solid product was collected by centrifugation and washed three times with water and anhydrous ethanol, respectively. The washed product was then dried in a 60 °C oven for 24 h.
[0037] Comparative Example 6: Preparation of Bi@BWO / BOC Catalytic Material and Its Application in Toluene Treatment The difference between the preparation of Bi@BWO / BOC and the preparation of Bi@BWO in Comparative Example 5 is that 12 mol / L HCl was added dropwise to adjust the pH of the solution to 3. Specifically: 120 mg of octadecyltrimethylammonium chloride was dissolved in 40 mL of water, followed by the addition of 300 mg of Na₂WO₄•2H₂O and 829 mg of Bi(NO₃)₃·5H₂O. After stirring for 60 min until completely dissolved, 30 mL of ethylene glycol was added, and then 12 mol / L HCl was added dropwise to adjust the pH of the solution to 3. After stirring for 30 min, the solution was transferred to a 100 mL Teflon-lined stainless steel autoclave for a solvothermal reaction at 150 °C for 24 h at a heating rate of 8 °C / min. After the reaction was completed, the solid product was collected by centrifugation and washed three times with water and anhydrous ethanol, respectively. The washed product was then dried in a 60 °C oven for 24 h.
[0038] Comparative Example 7: Preparation of Bi@BWO / BOS catalytic material and its application in toluene treatment The difference between the preparation of Bi@BWO / BOS and that of Comparative Example 5 is that 50 mg of thioacetamide was added to the solvothermal system, and the pH was adjusted to 8 by adding 6 mol / L NaOH solution. Specifically: 120 mg of octadecyltrimethylammonium chloride was dissolved in 40 mL of water, followed by the addition of 300 mg of Na₂WO₄•2H₂O and 829 mg of Bi(NO₃)₃·5H₂O. After stirring for 60 min until completely dissolved, 30 mL of ethylene glycol and 50 mg of thioacetamide were added. After stirring for 30 min, 6 mol / L NaOH was added dropwise to adjust the pH of the solution to 8. The solution was then transferred to a 100 mL Teflon-lined stainless steel autoclave for a solvothermal reaction at 150 °C for 24 h at a heating rate of 8 °C / min. After the reaction was complete, the solid product was collected by centrifugation and washed three times with water and anhydrous ethanol, respectively. The washed product was then dried in a 60 °C oven for 24 h.
[0039] Comparative Example 8: Application of Molecular Sieves Catalysts in the Treatment of Toluene, Formaldehyde, and Odor Toluene, formaldehyde, or methanethiol odors were removed using NKF-6(β) molecular sieves, and the performance testing methods were the same as in Example 1.
[0040] Comparative Example 9: Application of activated carbon catalysts in the treatment of toluene, formaldehyde, and odor. Activated carbon materials were used to remove toluene, formaldehyde, or methanethiol odors, and the performance testing methods were the same as in Example 1.
[0041] Experimental Example: Characterization of Different Catalytic Materials and Testing of Pollutant Treatment Performance 1. Characteristic representation: The catalysts of Examples 1-2 and Comparative Examples 1-7 were characterized by XRD, thermal imaging and other techniques. The results are as follows: Figure 1 The figures show the XRD patterns of catalysts Bi@BWO / BOC / BOS, BOS (Bi2O2S), BOC (BiOCl), Bi@BWO, and BWO. As can be seen from the figures, characteristic peaks belonging to Bi@BWO, BOC, and BOS can be found in the XRD diffraction peaks of Bi@BWO / BOC / BOS, indicating that (Bi@BWO) forms a heterojunction with bismuth oxychloride (BiOCl) and bismuth oxysulfide (Bi2O2S) through a tight interfacial bond.
[0042] The surface temperature of the Bi@BWO / BOC / BOS-M photothermal catalytic material prepared in Example 1 under illumination was recorded at... Figure 2 As can be seen from the figure, under illumination (optical density of 100 mW / cm²), 2 At λ=200-2500 nm, the surface temperature of Bi@BWO / BOC / BOS-M material can be stabilized at around 80℃, proving that the material has a good photothermal effect, which is beneficial to promoting photothermal catalytic reaction.
[0043] The Bi@BWO / BOC / BOS photothermal catalytic material prepared in Example 1 exhibits photochromic properties, such as... Figure 3 As shown, this demonstrates that the Bi@BWO / BOC / BOS material exhibits excellent photosensitivity.
[0044] 2. Testing of pollutant treatment performance: The removal capabilities of each catalyst in Examples 1-2 and Comparative Examples 1-9 for odor and VOCs were tested, and the results are as follows: A comparison of toluene removal efficiencies was made between Bi@BWO / BOC / BOS-M, Bi@BWO / BOC / BOS, BWO, Bi@BWO, Bi@BWO / BOC, Bi@BWO / BOS, and NKF-6(β) molecular sieves. Figure 4 As shown, the removal efficiency of toluene pollutant gas can be observed in the order of Bi@BWO / BOC / BOS-M>Bi@BWO / BOC / BOS>Bi@BWO / BOC>Bi@BWO / BOS>Bi@BWO>BWO>Molecular sieve. This indicates that after Bi@BWO and BWO / BOC form a heterostructure, Bi@BWO / BOC / BOS performs better than other reference catalysts, and the catalyst Bi@BWO / BOC / BOS and the modified molecular sieve have a synergistic effect in removing toluene.
[0045] A comparative study was conducted on the removal efficacy of Bi@BWO / BOC / BOS-M, Bi@BWO / BOC / BOS-C, NKF-6(β) molecular sieves and activated carbon materials for toluene, formaldehyde, and methanethiol odor. Figure 5-9 As shown, the Bi@BWO / BOC / BOS composite catalyst coupled with the adsorbent can achieve a faster removal effect for VOCs and odors.
[0046] In summary, this invention modifies ordinary bismuth tungstate material to prepare a heterojunction photothermal catalytic material (Bi@BWO / BOC / BOS) formed by the tight interfacial bonding of a bismuth tungstate (Bi2WO6) derivative (Bi@BWO), bismuth oxychloride (BiOCl), and bismuth oxysulfide (Bi2O2S). This material is then further coupled with a modified porous adsorbent to create a composite photothermal catalytic material. This composite photothermal catalytic material exhibits outstanding adsorption performance, achieving efficient purification of various VOCs and odorous gases without the need for an external heat source, and shows significant application potential in the field of indoor air purification.
[0047] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.
Claims
1. A method for preparing a composite photothermal catalytic material based on modified bismuth tungstate and a porous adsorbent, characterized in that, Includes the following steps: S1. Dissolve cationic surfactant and ethylene glycol in water, then add tungstate and bismuth salt, mix and dissolve, adjust the pH of the solution to 2-3 with HCl solution, add thioacetamide, dissolve and adjust the pH of the solution to 8-10 to carry out hydrothermal reaction, collect the solid product after reaction, wash and dry to obtain Bi@BWO / BOC / BOS photothermal catalyst. S2. Modified porous adsorbent is obtained by acid impregnation and drying. S3. Mix the Bi@BWO / BOC / BOS photothermal catalyst with the modified porous adsorbent, disperse it in the adhesive solution, coat it onto the felt, and dry it to obtain the composite photothermal catalytic material, wherein BWO is Bi2WO6, BOC is BiOCl, and BOS is Bi2O2S.
2. The method for preparing a composite photothermal catalytic material based on modified bismuth tungstate and a porous adsorbent according to claim 1, characterized in that, The cationic surfactant is selected from at least one of dodecyl dimethyl benzyl ammonium chloride, hexadecyl trimethyl ammonium chloride, octadecyl trimethyl ammonium chloride, and hexadecyl trimethyl ammonium bromide.
3. The method for preparing a composite photothermal catalytic material based on modified bismuth tungstate and a porous adsorbent according to claim 1, characterized in that, The tungstate includes Na2WO4•2H2O, and the bismuth salt includes Bi(NO3)3·5H2O.
4. The method for preparing a composite photothermal catalytic material based on modified bismuth tungstate and a porous adsorbent according to claim 1, characterized in that, The HCl solution used to adjust the pH of the solution in S1 is a 12 mol / L HCl solution, and the 6 mol / L NaOH solution is used to adjust the pH of the solution to 8-10; the hydrothermal reaction temperature is 100-250 ℃, and the time is 12-48 h.
5. The method for preparing a composite photothermal catalytic material based on modified bismuth tungstate and a porous adsorbent according to claim 1, characterized in that, The mass ratio of the tungstate, cationic surfactant, and thioacetamide is 250-350:30-300:40-60, and the molar ratio of the bismuth salt to the tungstate is (0.5-3):
1.
6. The method for preparing a composite photothermal catalytic material based on modified bismuth tungstate and a porous adsorbent according to claim 1, characterized in that, In S3, the mass ratio of the Bi@BWO / BOC / BOS photothermal catalyst to the modified porous adsorbent is (0.2-10):
1.
7. The method for preparing a composite photothermal catalytic material based on modified bismuth tungstate and a porous adsorbent according to claim 1, characterized in that, The porous adsorbent includes activated carbon and molecular sieves; the felt includes carbon felt, polymer felt, and fiber cloth; the adhesive solution is selected from at least one of polyvinyl alcohol, polyvinylpyrrolidone, polyurethane, and epoxy resin.
8. A composite photothermal catalytic material based on modified bismuth tungstate and a porous adsorbent prepared by the preparation method according to any one of claims 1-7.
9. The application of the composite photothermal catalytic material based on modified bismuth tungstate and porous adsorbent as described in claim 8 in the purification of VOCs and odor.
Citation Information
Patent Citations
Bismuth titanate / bismuth / bismuth vanadate composite photocatalyst and application of bismuth titanate / bismuth / bismuth vanadate composite photocatalyst in photo-thermal catalytic purification of organic gas pollutants
CN110368924A
Preparation method bismuth tungstate based multiple heterojunction photocatalyst
CN107537469A
Bismuth-bismuth sulfide-bismuth tungstate composite photocatalyst as well as preparation method and application thereof
CN114247452A